Case report: urinoma in the proximal thigh mimicking a soft tissue neoplasm - Schuppert, Christopher; Rehnitz, Christoph; Pecqueux, Carine; Angelescu, Michaela; Schlett, Christopher L. (Skeletal radiology, 2019)
Soft tissue tumors form a heterogeneous group of benign and malignant lesions. Those with a high fluid content may be particularly challenging in diagnosis. We present a 78-year-old man with a dolorous, progressive mass in the adductor region of the lower left extremity. At the end of a long diagnostic pathway, the pseudocystic tumor was eventually identified as a urinoma, caused by a prostatosymphyseal fistula that had occurred as a late complication of transurethral resection of the prostate. Our finding represents a rare variant of soft tissue tumors in the lower extremities, which MR-based urography can help to reveal.